Degree of conversion of resin cements polymerized under different thicknesses of feldspathic porcelain - Marcio Leandro Von Dreifus Marinho; Thaís Yumi Umeda Suzuki; Wirley Gonçalves Assunção; João Carlos Silos Moraes; Paulo Henrique dos Santos (Universidade Estadual de Campinas, 2019)
Aim The aim of this study is to evaluate the degree of conversion (DC) of resin cements polymerized under different thicknesses of feldspathic dental ceramic. Methods: Forty samples of RelyX ARC and RelyX Veneer resin cements were polymerized under Starlight feldspathic ceramic discs (DeguDent Gmbh) with 0.5 mm, 1.2 mm, 1.8 mm, and 2.4 mm in thickness. The control group was cured without the interposition of ceramic. The DC measurements were performed 10 minutes, 1 hour, and 24 hours after the light-activation in a Nexus 670 FTIR spectrophotometer. Data were analyzed by two-way repeated measure ANOVA and Fisher PLSD test. Results: The RelyX ARC showed higher DC for all ceramic thicknesses. There was significant decrease in DC related to an increase in ceramic thickness. For RelyX ARC, the values of DC obtained after 1 hour and 24 hours did not differ statistically between them, but they were higher than those analyzed after 10 minutes. For RelyX Veneer cement, there was gradual increase in the DC up to 24 hours. Conclusion: The higher the thicknesses of ceramic, the lower DC of the resin cement.